Volatile constituents of Hypericum asperulum Jaub. & Spach aerial parts from Iran - Boshra Azadi, (International Journal of Phytomedicine, 2013)
The essential oil composition of floweringaerial parts of Iranian endemic Hypericumasperulum Jaub. & Spach (Hypericaceae) was analyzed for the first timeby gas chromatography (GC) and gas chromatography–mass spectrometry (GC–MS).Forty five compounds representing 97.8% of the total oil were identified. Themain components were γ-Muurolene (13.1%), α-Pinene (12.2%),Germacrene D (11.3%), β-Caryophyllene(9.8%) and Spathulenol (7.2%). The volatile oil of Hypericum asperulumJaub. & Spach flowering aerial parts was characterized by high content ofsesquiterpene hydrocarbons (57.4%).